Penambahan Buah Jambu Biji Merah dalam Pembuatan Dodol Tepung Ketan dan Biji Nangka - Rahmayuni Rahmayuni; Dewi Fortuna Ayu; Yahya Riski Ashadi (Agriculture Faculty, 2025)
The purpose of this research was to get the best quality dodol based on the level use of red guava. The addition of red guava serves to increase the added value and benefits of the red guava and add flavor to dodol. This research was conducted experimentally using a completely randomized design (CRD) with four treatments and four replications. The data obtained were analyzed statistically using analysis of variance and continued with the Duncans Multiple Range Test (DMRT) at the 5% level. The treatments in this study were the addition of red guava based on total flour used with four levels; P1, P2, P3, and P4 (20%, 30%, 40%, and 50% of the total flour used). Parameters observed were moisture content, ash content, crude fiber content, total sugar content and sensory evaluation. The results showed that the use of red guava had a significant effect on all parameters. The best treatment in this study was P4 (the addition of red guava 50% of the total flour used) with a moisture content of 19.61%, ash content of 1.15%, fiber content of 12.72% and sucrose content 41.13% and the overall sensory assessment was favored by the panelists.